Arterio‐venous fistula for automated red blood cells exchange in patients with sickle cell disease: Complications and outcomes. Issue 2 (7th December 2016) - Delville, Marianne; Manceau, Sandra; Ait Abdallah, Nassim; Stolba, Jan; Awad, Sameh; Damy, Thibaud; Gellen, Barnabas; Sabbah, Laurent; Debbache, Karima; Audard, Vincent; Beaumont, Jean‐Louis; Arnaud, Cécile; et al.
Abstract : Erythrocytapheresis (ER) can improve outcome in patients with sickle cell disease (SCD). A good vascular access is required but frequently it can be difficult to obtain for sickle cell patients. Arterio‐venous fistulas (AVFs) have been suggested for ER in SCD supported by limited evidence. We report the largest cohort of ER performed with AVFs from three French SCD reference centers. Data of SCD patients undergoing ER with AVFs in the French SCD reference center were retrospectively collected. The inclusion criteria were: SS or Sβ‐Thalassemia and AVF surgery for ER. SCD‐related complications, transfusion history, details about AVF surgical procedure, echocardiographic data before and after AVF, AVF‐related surgical and hemodynamical complications were collected. Twenty‐six patients (mean age 20.5 years, mean follow‐up 68 months [11–279]) were included. Twenty‐three patients (88.5%) required central vascular access before AVF. Fifteen AVFs (58%) were created on the forearm and 11 (42%) on the arm. Nineteen patients (73%) had stenotic, thrombotic or infectious AVF complications. A total of 0.36 stenosis per 1, 000 AVF days, 0.37 thrombosis per 1, 000 AVF days and 0.078 infections per 1.000 AVF days were observed. The mean AVF lifespan was 51 months [13–218]. One patient with severe pulmonary hypertension worsened after AVF creation and died. We report the first series of SCD patients with AVF for ER, demonstrating that AVFs could be considered as a potential vascular access for ER. Patients with increased risk for hemodynamic intolerance of AVFs must be carefully identified, so that alternative vascular accesses can be considered. Am. J. Hematol. 92:136–140, 2017. © 2016 Wiley Periodicals, Inc.